Belt and Road Initiative : alternative development path for Africa - Managa, Lavheselani Rodney; Simelane, Thokozani (Africa Institute of South Africa, 2018)
China's emphasis on infrastructure development has received support from African leaders. Its focus on infrastructure development in Africa was endorsed by the signing of a Memorandum of Understanding between China and the African Union on 27 January 2015. The agreement outline plans for connecting African countries through transportation infrastructure projects, including modern highways, airports, and high speed railways. At the heart of Belt and Road Initiative lies the creation of an economic land belt that includes countries on the original Silk Road through Central Asia, the Middle East and Europe, as well as a maritime "road" that links China's port facilities with the African coast, pushing up through the Suez Canal into the Mediterranean. China has from the outset emphasised that the Belt and Road Initiative will be developed within the framework of the five principles. These entails mutual respect for each other's territorial integrity and sovereignty; non-aggression; non-interference in each other's internal affairs; equality and mutual benefit; and peaceful coexistence. This volume provides an analysis of this stance by both African and Chinese scholars. Africa through its Agenda 2063 has been driving, among others, the re-industrialisation of its economies, improved connectivity and infrastructure development, diversification of energy sources, technology transfer and skills development. The Belt and Road Initiative provides an alternative path for Africa to realise some of these milestones